Effects of Ni on the electrochemical properties of Ni-C nanocomposites prepared by one-step ion beam irradiation - Gupta, Vikaskumar Pradeepkumar; Akiyama, Tatsuya; Yaakob, Yazid; Suryavanshi, Ulka; Asaka, Toru; Ishii, Yosuke; Miyazaki, Hidetoshi; Kawasaki, Shinji; Hihara, Takehiko; Tanemura, Masaki (Springer, 2026)
Supercapacitors are superior in terms of long cycle life and power delivery which makes it more efficient in many applications. Here we propose the effect on capacitance by varying the concentration of Ni and C electrode material deposited on Au as the current collector electrode by ion beam irradiation method, which assists in the processing and engineering of new material. For the electrode fabrication, Au foil was irradiated with Ar + ions with simultaneous supply of Ni and C with various Ni/C ratios by ion beam irradiation method at room temperature and labeled as NiC-1, NiC-2, and NiC-3. Through SEM imaging, a distinct nanoprotrusion was identified. Successful control of nickel supply was affirmed via results obtained by inductively coupled plasma mass spectrometry (ICP-MS), revealing nickel concentrations of 3.9 µg/cm2, 14 µg/cm2, 30 µg/cm2 in the respective samples NiC-1, NiC-2, and NiC-3. The high-resolution transmission electron microscopy (TEM) observation unveiled a uniform distribution of Ni nanoparticles (Ni NPs) within a carbon matrix. Cyclic voltammetry (CV) measurement demonstrated typical faradaic redox reactions across all samples. Electrochemical assessment indicated that higher carbon content correlated with enhanced reaction efficiency, suggesting a potential extension in the life cycle of the pseudocapacitor. Notably, constant current and CV measurements highlighted superior performance in the sample NiC-1. In conclusion, the proposed pseudocapacitor configuration, NiC-1 (656 Fg−1), holds promise for enhanced performance.